CONCEPTION OF EDUCATION AND SEARCH OF OIL AND GAZ - Єсипович, С. М. (Ukrainian journal of remote sensing, 2015)
Favorable conditions for the formation of high output deposits occur in the most mobile areas of the crust so-called suture riftzones (SRZ). Mechanical conditions of “grinding” and forced filtration of juvenile hydrocarbons through dynamically strainedlayers, rich in organic matter, are supplemented by the conditions of high temperature and pressure. Study of the SRZ providesfor defining of a specified structural model of a prospecting site and determines the place for a test well in the anticline arch.